FRP deck and steel girder bridge systems : analysis and design - Davalos, Julio F. (Composite materials (Boca Raton, Fla.), 2013)
"This book presents the analysis and design of fiber-reinforced polymer (FRP) decks, which have been increasingly implemented in rehabilitation projects and new construction due to their reduced weight, lower maintenance costs, and enhanced durability and service life. The book is organized into three complementary parts, covering FRP decks, shear connectors between the deck and steel girders, and the behavior of bridge systems. It outlines analysis and design guidelines for each specific deck type, which can be broadly classified according to their production process as sandwich panels and adhesively bonded cellular sections, produced mainly by pultrusion"--